Evaluation of specific value of endoscopic biopsies and brush cytology for malignancies of the oesophagus and stomach. Issue 5 (May 1976) - Witzel, L; Halter, F; Grétillat, P A; Scheurer, U; Keller, M
Abstract : The value of multiple biopsies and brush cytology at oesophago-gastroscopy was assessed in relation to macroscopy and localization on 100 verified tumours in a prospective study. The cumulative accuracy achieved was 96%. This was significantly better (P less than 0-01) than that of biopsy (83%) and of cytology (85%). While the reliability of both procedures was not significantly different in malignancies of the oesophagus, the gastric body, and the antrum, cytoloty was significantly more accurate in cancers of the cardia (90% and 55% respectively, P less than 0-05). Cytology was also more reliable in stenosing tumours (92%/72%, P less than 0-05). In polypoid malignancies a positive but not significant trend was found in favour of multiple biopsies (94%/64%). One of the two early cancers was only diagnosed by cytology. The results confirm the high diagnostic accuracy of multiple endoscopic biopsies combined with brush cytology and demonstrate the value of cytology in stenosing tumours, especially in those of the cardia.